Transparent exopolymer particles (TEP), coomassie stainable particles (CSP) and Surfactants measurements from the central artic ... - Robinson, Tiera-Brandy (PANGAEA, 2024)
As part of the MOCCHA 2018 campaign onboard I/B Oden, Sea surface microlayer (SML) and underlying water (ULW) samples were taken from an open lead system in the central arctic. Sampling occurred during the autumn freeze-up from 18.08.18 - 08.09.18. Latitude ranged from 88.7644-89.5474 degrees and longitude ranged from -129.5000 - 47.998700 degrees as the ice pack moved over time. Sea surface microlayer samples were collected using the glass plate technique (Harvey and Burzell, 1972, doi:10.4319/lo.1972.17.1.0156) via rotating glass disks equipped to a catamaran and underlying water samples were collected from 1 meter depth. Seven variables were sampled for; transparent exopolymer particles (TEP), coomassie stainable particles (CSP), surfactants, chlorophyll a, particulate organic carbon (POC), particulate organic nitrogen (PON) and particulate organic phosphorous (POP). Replicate concentrations of TEP and CSP are presented here in micrograms per liter using the spectrophotometric method (Passow and ...